Staphylococcus aureus still the commonest culprit - Kumar, Saurabh; Faisal, Yousuf; Chaudhary, Rajib Ratan; Sarda, Mukund Shyam (International Journal of Research in Medical Sciences, 2020)
Background: Sepsis is still one of the most leading cause of death in world. 19 million sepsis (formerly severe sepsis) cases and 5 million sepsis-related deaths are estimated to occur annually. Sepsis is also one of the most common cause of patients getting critically ill and getting admission in intensive care unit. The main focus of this study is to identify the culture isolate from the critically ill patients and to check for the antibiotic sensitivity and resistance and identify if the report has changed the course of treatment and outcome of the patients. Critical illness is a life-threatening multisystem process that can result in significant morbidity or mortality. Critically ill patients are those who have dysfunction or failure of one or more organs/system and depend on survival from advanced instruments of monitoring and therapy. The aim of the study was to identify the causative organism causing sepsis in critically ill patients. Methods: It will be multi central retrospective study which included patients of critical illness of Rohilkhand Medical college, Bareilly, Uttar Pradesh and Varun Arjun Medical college, Shahjanpur, A total of 468 patients were taken for the analysis during period of from August 2018 to November 2019 among of which 324 samples came positive. Samples were taken on day one of the patient’s presentation to the hospital and were analysed in BD BACTEC culture medium. Patient’s data were taken from records available at both the hospitals. Sensitivity was performed using disk diffusion method and the results were compared with the records of patients. Results: Among of samples taken that is 324; 194 were male and 130 were female. Maximum patients which were tested positive for Staphylococcus aureus (n=198). Others included Streptococcus pneumococcus (n=25), Escherichia coli (n=50), Klebsiella oxytoca (n=13), Klebsiella pneumoniae (n=15), Pseudomonas aeruginosa (n=20), and Acinetobacter (n=3). In retrospective analysis of the patients of all 324 cases treatment in approximately 148 patients was changed due to change in the sensitivity of antibiotics. Conclusions: Staphylococcus still dominates the sepsis. It is advisable to add an antibiotic with gram negative if patients count does not improve in first 24 hour.